СИНХРОННОЕ РЕГУЛИРОВАНИЕ СДВОЕННЫХ ИНВЕРТОРОВ С ОТСЕКАЮЩИМИ ДИОДАМИ ДЛЯ ФОТОПРЕОБРАЗОВАТЕЛЬНОЙ УСТАНОВКИ - Олещук, В.; Ермуратский, В. (Інститут електродинаміки НАН України, Київ, 2015)
Modulation processes have been analyzed in transformer-based photovoltaic system on the basis of cascaded diode-clamped inverters, adjusted by special control scheme with the use of specific voltage vectors. It has been shown, that symbiosis of this control scheme with algorithms of synchronous modulation insures minimization of common-mode voltage and magnitudes of even harmonics and subharmonics in spectra of voltage on the primary side of three-phase transformer. Simulations validate operation of this system with three control techniques. References 10, figures 6.